Thermal Scanning System Using Arduino Nano - Zamfir, E M; Miruna Avram; Radu, M; Stănescu, C; Preduşcă, G (The scientific bulletin of Electrical Engineering Faculty, 2023)
The paper presents the study and implementation of a thermal scanning system that collects and transmits in real time the thermal data of scanned objects for their constant monitoring using an infrared temperature sensor and an Arduino Nano board. The application is made with the Arduino IDE, with the help of which the control of the Arduino board, sensors, screen, and LEDs connected to the platform is conducted. The sensors create the overall image of the thermal scan and send it to the Liquid-Crystal Display Thin-Film Transistor (LCD TFT) screen, and if an anomaly occurs, the red LED lights up.